Exploring the Past Biosphere of Chew Bahir/Southern Ethiopia: Cross-Species Hybridization Capture of Ancient Sedimentary DNA from a Deep Drill Core - Krueger, Johanna; Foerster, Verena; Trauth, Martin H.; Hofreiter, Michael; Tiedemann, Ralph (Frontiers in Earth Science, 2021)
Eastern Africa has been a prime target for scientific drilling because it is rich in key paleoanthropological sites as well as in paleolakes, containing valuable paleoclimatic information on evolutionary time scales. The Hominin Sites and Paleolakes Drilling Project (HSPDP) explores these paleolakes with the aim of reconstructing environmental conditions around critical episodes of hominin evolution. Identification of biological taxa based on their sedimentary ancient DNA (sedaDNA) traces can contribute to understand past ecological and climatological conditions of the living environment of our ancestors. However, sedaDNA recovery from tropical environments is challenging because high temperatures, UV irradiation and desiccation result in highly degraded DNA. Consequently, most of the DNA fragments in tropical sediments are too short for PCR amplification. We analyzed ancient DNA in the upper 70 m of the composite sediment core of the HSPDP drill site at Chew Bahir for eukaryotic remnants. We first tested shotgun high throughput sequencing which leads to metagenomes dominated by bacterial DNA of the deep biosphere, while only a small fraction was derived from eukaryotic, and thus probably ancient, DNA. Subsequently, we performed cross-species hybridization capture of sedaDNA to enrich ancient DNA from eukaryotic remnants for paleoenvironmental analysis, using established barcoding genes (cox1 and rbcL for animals and plants, respectively) from 199 species that may have had relatives in the past biosphere at Chew Bahir. Metagenomes yielded after hybridization capture are richer in reads with similarity to cox1 and rbcL in comparison to metagenomes without prior hybridization capture. Taxonomic assignments of the reads from these hybridization capture metagenomes also yielded larger fractions of the eukaryotic domain. For reads assigned to cox1, there was a notable coincidence between high absolute read numbers and a wet climate (as inferred from potassium count rates). Furthermore, inferred wet periods were associated with high inferred abundances of putatively limnic organisms (gastropods, green algae), while inferred dry periods showed increased numbers for higher plants. These findings indicate that cross-species hybridization capture can be an effective approach to enhance the information content of sedaDNA in order to explore biosphere changes associated with past environmental conditions around paleo-lake Chew Bahir and beyond.